Interobserver Variability and Distribution of Mammographic Breast Density in Patients with Invasive Breast Carcinoma using the Fifth Edition of BI-RADS Guidelines - Siti Soraya Ab Rahman; Mohd Kamal L.H.; Ab Rahman F.H.; Ghazali R.; Saidil E.; Mohamad Nor N. (Kulliyyah of Medicine, International Islamic Unive, 2024)
Indexed by WOS/Scopus/MyCite